Cognitive Control Performance as Measured by Clustering and Switching in Nepali – English Bilingual Verbal Fluency Task - Pathak, Lekhnath Sharma; Pathak, Nishan; Pathak, Aarya (Gipan, 2024)
Verbal fluency task is a simple yet powerful neuropsychological tool for measuring linguistic and cognitive processing. In this research article we report the clustering and switching, as identified by Troyer and colleagues (1997), as cognitive control measured through semantic and phonetic verbal fluency task. We tested 25 Nepali (L1) - English (L2) bilingual adults with mean age of 22 years on f, a, s for English phonemic fluency, s, k, d for Nepali phonetic fluency and animals, cloths, vegetables, fruits and flowers for semantic fluency in both Nepali and English. The participants performed better in L2 phonetic fluency compared to L1 phonetic fluency, whereas, there was mixed results in semantic output in both the languages. They exhibited more clusters in phonetic fluency compared to semantic fluency in both L1 and L2 which indicates participants needed to disengage from the previous strategy or subcategory and move on to the next strategy or subcategory, thus, reflecting more cognitive demand imposed by the phonetic fluency compared to semantic fluency. This is the first such study with Nepali – English bilinguals. This study may further be extended to include more diversified population in terms of age, language family, typicality and ethnicity as independent variables.